Choroidal Metastatic Carcinoma Accompanied With Sjögren Syndrome Initially Presenting as Acute Glaucoma With Angle Closure: Case Report - Chen, Chunli; Hu, Feng; Cheng, Yizhe; Hu, Zhixiang; Wang, Ge; Peng, Xiaoyan (Frontiers in Ophthalmology, 2022)
Background To report a case of choroidal metastatic carcinoma accompanied by Sjögren syndrome (SS) initially presenting as acute glaucoma with angle closure. Case Presentation A 47-year-old woman complaining about swelling pain and blurred vision in the right eye for 3 days had a notable previous history of dry eyes, dry mouth, and joint pain. In another clinic, she was misdiagnosed as having acute glaucoma with angle closure, but she had poor response to eye drops and intravenous drip of mannitol for controlling intraocular pressure. The intraocular pressure in the right eye was 49 mm Hg, yet with clear cornea, shallow peripheral anterior chamber depth with 1/4 cornea thickness and fixed and dilated pupil. Macular folds were noted through a 90-D lens via slit lamp. Therefore, the diagnosis of secondary glaucoma was considered. Further examinations were conducted. Ultrawide-field fundus image showed retinal detachment with choroidal detachment in the right eye with suspected solid occupation of choroid metastatic cancer. B-scan ultrasound showed an elevated mass in the posterior pole of the ocular wall. The patient showed very good response to local corticosteroid eye drops after 3 days with deepening of the anterior chamber and significant decline of intraocular pressure. The brain, ocular magnetic resonance imaging, and lung computed tomography with enhancement showed lung cancer and choroidal metastatic carcinoma. Immunological abnormalities and symptoms supported the diagnosis of SS. After 1-month systematic chemotherapy and local–regional radiotherapy, retinal and choroidal detachment was restored with a stable intraocular pressure. Conclusion The ophthalmologist should pay attention to differential diagnosis of angle-closure glaucoma from secondary glaucoma in cases with choroidal–retinal detachment or macular folds, which could be an ocular manifestation of choroidal metastatic carcinoma or SS in rare condition.